2006
DOI: 10.1086/502973
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Influenza C Virus Infection in Children

Abstract: Influenza C virus is a significant cause of upper-respiratory-tract illness in children < 6 years old, and the risk of complications with lower-respiratory-tract illness is particularly high in children < 2 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
152
3
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(171 citation statements)
references
References 29 publications
11
152
3
3
Order By: Relevance
“…However, these numbers are still below the ideal and have also been observed in other cities in South and Southeast Brazil, such as São Paulo/SP, Rio de Janeiro/RJ, Curitiba/ PR, and Florianópolis/SC 17,18 that have shown coverage under 80%, according recent studies 19,20 . This study showed that there are some factors related to nonadherence of elderly people to vaccination campaigns that may be linked to the lower observed coverage.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, these numbers are still below the ideal and have also been observed in other cities in South and Southeast Brazil, such as São Paulo/SP, Rio de Janeiro/RJ, Curitiba/ PR, and Florianópolis/SC 17,18 that have shown coverage under 80%, according recent studies 19,20 . This study showed that there are some factors related to nonadherence of elderly people to vaccination campaigns that may be linked to the lower observed coverage.…”
Section: Discussionmentioning
confidence: 90%
“…Systemic reactions such as fever, malaise and myalgia can also occur, usually 6 to 12 hours after vaccination, lasting one to two days. Hypersensitivity reactions, anaphylaxis and neurological manifestations are extremely rare [18][19][20][21] . Based on the exposed, the purpose of this study was to estimate An interview was performed by a trained medical student present at the Health Unit two days a week over 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Influenza C virus is ubiquitous and usually causes a mild upper respiratory tract illness in children and lower respiratory tract illnesses such as bronchitis and pneumonia in infants and children (1,2). To clarify the epidemiology of acute viral respiratory infections in children in Yamagata, Japan, as a part of the National Epidemiological Surveillance of Infectious Diseases, Japan based on the Infectious Diseases Control Law, we performed virus isolation using HHVM, HHVMRG, and HHVe6MRG microplates, containing HEF, HEp-2, Vero or VeroE6, MDCK, RD-18S, and GMK cell lines as well as the HMV-II cell line, in part, for the isolation of viruses, including influenza virus C (1,3-7).…”
Section: Communicated By Takato Odagirimentioning
confidence: 99%
“…41 Rhinorrhoea occurs commonly. The classic symptoms are sudden onset of fever, with or without chills, headache, malaise, and cough.…”
Section: Symptomsmentioning
confidence: 99%